(untitled) (Global Journal of Human-Social Science, 2017)
Graduate employability is a key concept in political economic and social discourse There is no generally accepted definition of graduate employability In this regard researcher critically review the graduates unemployment in the Sri Lankan and the Global context Extensive review strains to focalize on the factors influencing graduate unemployment such as skill mismatch education mismatch In addition with the general factors the lack of coordination and cooperation among the various stakeholders of universities become a root cause for unemployment